T cells engrafted with a UniCAR 28/z outperform UniCAR BB/z-transduced T cells in the face of regulatory T cell-mediated immunosuppression. (2nd September 2019) - Kegler, Alexandra; Koristka, Stefanie; Bergmann, Ralf; Berndt, Nicole; Arndt, Claudia; Feldmann, Anja; Hoffmann, Anja; Bornhäuser, Martin; Schmitz, Marc; Bachmann, Michael P.
ABSTRACT: Adoptive transfer of chimeric antigen receptor (CAR)-equipped T cells have demonstrated astonishing clinical efficacy in hematological malignancies recently culminating in the approval of two CAR T cell products. Despite this tremendous success, CAR T cell approaches have still achieved only moderate efficacy against solid tumors. As a major obstacle, engineered conventional T cells (Tconvs) face an anti-inflammatory, hostile tumor microenvironment often infiltrated by highly suppressive regulatory T cells (Tregs). Thus, potent CAR T cell treatment of solid tumors requires efficient activation of Tconvs via their engrafted CAR to overcome Treg-mediated immunosuppression. In that regard, selecting an optimal intracellular signaling domain might represent a crucial step to achieve best clinical efficiency. To shed light on this issue and to investigate responsiveness to Treg inhibition, we engrafted Tconvs with switchable universal CARs (UniCARs) harboring intracellularly the CD3ζ domain alone or in combination with costimulatory CD28 or 4-1BB. Our studies reveal that UniCAR ζ-, and UniCAR BB/ζ-engineered Tconvs are strongly impaired by activated Tregs, whereas UniCARs providing CD28 costimulation overcome Treg-mediated suppression both in vitro and in vivo . Compared to UniCAR ζ- and UniCAR BB/ζ-modified cells, UniCAR 28/ζ-armed Tconvs secrete significantly higher amounts of Th1-related cytokines and, furthermore, levels of these cytokines are elevated even upon exposure to Tregs. Thus, in contrast to 4-1BB costimulation, CD28 signaling in UniCAR-transduced Tconvs seems to foster a pro-inflammatory milieu, which contributes to enhanced resistance to Treg suppression. Overall, our results may have significant implications for CAR T cell-based immunotherapies of solid tumors strongly invaded by Tregs.